Sociodrama Method; Stimulate the Development of Attitudes, Knowledge and Skills of Students in Excellent Service Learning - Brillian Rosy (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
Implementation of the Curriculum 2013 expects students not only memorize the theory, but is expected to practice it or apply it to gain knowledge, skills and attitude development so that the quality of education to be good. There are some materials in Service Excellence subject, among others are as follows: a) Standard of Personal Appearance, b) Prime Service Principle, c) Providing Help to Customers, and d) Communication with Customers. However, some knowledge materials in the Excellent Service such as how to provide assistance to customers and communicate with customers are difficult to understand by students when teachers explain by lecture method. This can hamper the creativity and skill of the students because the learning only takes one direction, while the material presented is the material that is practical and demands the skills of the students. Direct practice or demonstration is meant for students to imagine and feel as though they are in real situations when the excellent service is performed. Learning process like this, requires a learning method that can support the learning objectives. The Sociodrama method is a teaching method in which the teacher provides the opportunity for the pupil to perform certain role playing activities as found in the life of the social community. The conceptual review in this article proves that the Sociodrama method has successfully stimulated the development of students' attitudes, knowledge and skills in Learning service excellence